2011
DOI: 10.4028/www.scientific.net/amr.356-360.1660
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Gas-Phase Elemental Mercury by Bromine-Impregnated Activated Carbon

Abstract: Br-impregnated activated carbon for gas-phase elemental mercury adsorption experiments were carried out at a fixed-bed system to get the suitable mass fraction of KBr impregnation solution. Hg removal efficiency of 1% wt KBr-ACs was 69.0%, while that of 10% wt KBr-ACs was 57.9%. Both of them were higher than that of the raw activated carbon, 42.2%. The removal efficiency of Hg0 was not proportional to bromine concentration. Under 80-180°C, Hg removal efficiency of 1% wt KBr-ACs were 68.3%-71.8%, and at 140°C i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Since the dynamic test was carried out at room temperature, adsorption of mercury is attributed to physisorption . The chemical structure could play an important role in mercury adsorption …”
Section: Resultsmentioning
confidence: 99%
“…Since the dynamic test was carried out at room temperature, adsorption of mercury is attributed to physisorption . The chemical structure could play an important role in mercury adsorption …”
Section: Resultsmentioning
confidence: 99%
“…It was also observed that graft modification resulted in an increase in average pore diameter, indicating that the blocked pores would be micropores [49]. For the pure physical adsorption process, the adsorption capacity increases with the increasing surface area of the adsorbent [50]. Note that the untreated corn royalsocietypublishing.org/journal/rsos R. Soc.…”
Section: Elemental Analysismentioning
confidence: 96%
“…But for Pb(II), the Freundlich model fitted better as the value of R 2 = 0.99328. Both Langmuir and Freundlich isotherms may adequately describe the same set of data for liquidsolid adsorption over a range of concentrations, especially if the solution concentration is small and the adsorption capacity of the solid is large enough to make both isotherm equations approach a linear form [50]. The reusability of adsorbents is an important factor for the cost reductions in practical application [22,61].…”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…In carbon injection technologies, various chemically treated carbons were developed to enhance the elemental mercury removal efficiency including sulfur impregnation, 8,9 chloride impregnation 10,11 and bromination. 12,13 Among these chemical treatments, brominated sorbents appeared to be one of the most effective systems with 70% to 90% removal efficiency. 12,13 Most brominated sorbents involved the use of Br 2 vapors.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Among these chemical treatments, brominated sorbents appeared to be one of the most effective systems with 70% to 90% removal efficiency. 12,13 Most brominated sorbents involved the use of Br 2 vapors. However, the corrosive property of Br 2 vapor may cause problems in handling and processing.…”
Section: Introductionmentioning
confidence: 99%